COVID‐19 Outcomes in Patients With Systemic Autoimmune Rheumatic Diseases Compared to the General Population: A US Multicenter, Comparative Cohort Study. Issue 6 (1st May 2021) - D'Silva, Kristin M.; Jorge, April; Cohen, Andrew; McCormick, Natalie; Zhang, Yuqing; Wallace, Zachary S.; Choi, Hyon K.
Abstract : Objective: Patients with systemic autoimmune rheumatic diseases (ARDs) continue to be concerned about risks of severe coronavirus disease 2019 (COVID‐19) outcomes. This study was undertaken to evaluate the risks of severe outcomes in COVID‐19 patients with systemic ARDs compared to COVID‐19 patients without systemic ARDs. Methods: Using a large multicenter electronic health record network, we conducted a comparative cohort study of patients with systemic ARDs diagnosed as having COVID‐19 (identified by diagnostic code or positive molecular test result) compared to patients with COVID‐19 who did not have systemic ARDs, matched for age, sex, race/ethnicity, and body mass index (primary matched model) and additionally matched for comorbidities and health care utilization (extended matched model). Thirty‐day outcomes were assessed, including hospitalization, intensive care unit (ICU) admission, mechanical ventilation, acute renal failure requiring renal replacement therapy, ischemic stroke, venous thromboembolism, and death. Results: We initially identified 2, 379 COVID‐19 patients with systemic ARDs (mean age 58 years; 79% female) and 142, 750 comparators (mean age 47 years; 54% female). In the primary matched model (2, 379 patients with systemic ARDs and 2, 379 matched comparators with COVID‐19 without systemic ARDs), patients with systemic ARDs had a significantly higher risk of hospitalization (relative risk [RR] 1.14 [95% confidence interval (95% CI) 1.03–1.26]), ICU admission (RR 1.32 [95% CI 1.03–1.68]), acute renal failure (RR 1.81 [95% CI 1.07–3.07]), and venous thromboembolism (RR 1.74 [95% CI 1.23–2.45]) versus comparators but did not have a significantly higher risk of mechanical ventilation or death. In the extended model, all risks were largely attenuated, except for the risk of venous thromboembolism (RR 1.60 [95% CI 1.14–2.25]). Conclusion: Our findings indicate that COVID‐19 patients with systemic ARDs may be at a higher risk of hospitalization, ICU admission, acute renal failure, and venous thromboembolism when compared to COVID‐19 patients without systemic ARDs. These risks may be largely mediated by comorbidities, except for the risk of venous thromboembolism.